Mindfulness como estratégia terapêutica para o zumbido: uma revisão sistemática e de escopo - Garcia, Ana Luiza Caldas (2021)
Tinnitus is the perception of a sound in the absence of an acoustic stimulus very associated with hearing difficulties, but it can have much greater psychological effects. This symptom can affect the quality of life, involving sleep disorders, impaired work and psychiatric suffering. Mindfulness is a therapy that has been used in health to reduce stress, pain, anxiety and also for tinnitus. This study aims to verify, through systematic review, whether mindfulness is an effective therapy for chronic tinnitus in adults, when compared to other treatments. This systematic review was outlined and reported following the recommendations of PRISMA and recorded in PROSPERO. Electronic and manual searches were carried out in 9 databases. The search was carried out by peers on April 17, 2020, according to the PICOS strategy previously outlined: P- adult with chronic tinnitus, I- mindfulness, C- other therapy or no therapy, O-improvement in tinnitus perception and S- randomized clinical trials. The selection of the studies was carried out in two moments independently by two researchers and the discrepancies were resolved by a third researcher. After selection, the articles were evaluated with the aid of the Cochrane Risk of Bias Tool 2.0 - RoB 2.0, used to evaluate randomized clinical trials. Through the search strategy, a total of 402 studies were found in the 9 databases searched, but in the end only 3 met the inclusion and exclusion criteria. In this systematic review it was possible to conclude that mindfulness can be used as therapy for the treatment of chronic tinnitus in the adult population.